2022
DOI: 10.32604/cmc.2022.032083
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain Assisted Intrusion Detection System Using Differential Flower Pollination Model

Abstract: Cyberattacks are developing gradually sophisticated, requiring effective intrusion detection systems (IDSs) for monitoring computer resources and creating reports on anomalous or suspicious actions. With the popularity of Internet of Things (IoT) technology, the security of IoT networks is developing a vital problem. Because of the huge number and varied kinds of IoT devices, it can be challenging task for protecting the IoT framework utilizing a typical IDS. The typical IDSs have their restrictions once execu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Lastly, sailfish optimizer (SFO) with RBM technique is utilized for effective identification of intrusions. In [12], the authors suggested BC deep-rooted Bi-level ID and graph-based mitigation model called Hybrid-Chain-IDS. Primarily, time-based authentication to validate the legal users utilizing the NIK512 hashing procedure is performed.…”
Section: Related Workmentioning
confidence: 99%
“…Lastly, sailfish optimizer (SFO) with RBM technique is utilized for effective identification of intrusions. In [12], the authors suggested BC deep-rooted Bi-level ID and graph-based mitigation model called Hybrid-Chain-IDS. Primarily, time-based authentication to validate the legal users utilizing the NIK512 hashing procedure is performed.…”
Section: Related Workmentioning
confidence: 99%